The first non-aristonectine elasmosaurid (Sauropterygia; Plesiosauria) cranial material from Antarctica: New data on the evolution of the elasmosaurid basicranium and palate - O'gorman, Jose Patricio; Coria, Rodolfo Anibal; Reguero, Marcelo Alfredo; Santillana, Sergio; Mörs, Thomas; Cardenas, Magali (Cretaceous Research)
Elasmosaurids are a monophyletic group of cosmopolitan plesiosaurs with extremely long necks. Although abundant elasmosaurid material has been collected from the Upper Cretaceous of Antarctica, skull material is extremely rare. Here, new elasmosaurid cranial material from the lower Maastrichtian levels of the Cape Lamb Member (Snow Hill Island Formation) on Vega Island, Antarctica is described. The studied specimen (MLP 15-I-7-6) is a non-aristonectine elasmosaurid but shows a palate morphology characterized by the absence of a posterior interpterygoid symphysis and a posterior plate-like extension of the pterygoids, features previously associated with the aristonectine palatal structure. The specimen MLP 15-I-7-6 thus provides an indication that these palatal features are also present in non-aristonectine Weddellian elasmosaurids, and makes available additional evidence of the close phylogenetical relationship between the aristonectines and some Weddellian non-aristonectine elasmosaurids. Fil: O'gorman, Jose Patricio. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata; Argentina Fil: Coria, Rodolfo Anibal. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Provincia del Neuquén. Municipalidad de Plaza Huincul. Museo "Carmen Funes"; Argentina Fil: Reguero, Marcelo Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores, Comercio Internacional y Culto. Direccion Nacional del Antártico; Argentina Fil: Santillana, Sergio. Ministerio de Relaciones Exteriores, Comercio Internacional y Culto. Direccion Nacional del Antártico; Argentina Fil: Mörs, Thomas. Naturhistoriska Riksmuseet; Suecia Fil: Cardenas, Magali. Universidad Nacional de Río Negro; Argentina